Effect of Fiber Posts on Stress Distribution of Endodontically Treated Upper Premolars: Finite Element Analysis - Zarow, Maciej (Nanomaterials (Basel), 2020)
By means of a finite element method (FEM), the present study evaluated the effect of fiber post (FP) placement on the stress distribution occurring in endodontically treated upper first premolars (UFPs) with mesial–occlusal–distal (MOD) nanohybrid composite restorations under subcritical static load. FEM models were created to simulate four different clinical situations involving endodontically treated UFPs with MOD cavities restored with one of the following: composite resin; composite and one FP in the palatal root; composite and one FP in the buccal root; or composite and two FPs. As control, the model of an intact UFP was included. A simulated load of 150 N was applied. Stress distribution was observed on each model surface, on the mid buccal–palatal plane, and on two horizontal planes (at cervical and root-furcation levels); the maximum Von Mises stress values were calculated. All analyses were replicated three times, using the mechanical parameters from three different nanohybrid resin composite restorative materials. In the presence of FPs, the maximum stress values recorded on dentin (in cervical and root-furcation areas) appeared slightly reduced, compared to the endodontically treated tooth restored with no post; in the same areas, the overall Von Mises maps revealed more favorable stress distributions. FPs in maxillary premolars with MOD cavities can lead to a positive redistribution of potentially dangerous stress concentrations away from the cervical and the root-furcation dentin.